THE IMPORTANCE OF PRIMARY TEETH IN CHILDREN AND MEASURES FOR THEIR PRESERVATION - Abduraxmonova, Shohista (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
This article discusses the vital role of primary (deciduous) teeth in the growth and development of children, emphasizing their importance for nutrition, speech formation, facial structure, and the proper eruption of permanent teeth. Despite being temporary, primary teeth play a fundamental role in maintaining oral health and overall well-being during early childhood. The paper highlights the most common causes of premature tooth loss, such as dental caries, trauma, and poor oral hygiene, and examines the preventive strategies necessary to protect these teeth. The importance of parental awareness, regular dental check-ups, and early education on oral hygiene habits is also underscored. Effective preventive care not only ensures healthy primary teeth but also supports the long-term health of the permanent dentition and the development of a confident, healthy smile in children.